Samorząd zawodowy w systemie ustrojowym Polski - Kmieciak, Robert (Polityka i Społeczeństwo, 2021)
The socio-political changes which began in Poland over three decades ago resulted in, inter alia, the activation of various occupational groups that have decided to operate on the basis of the then existing public law. This meant the creation of corporate selfgovernment organizations that are based on associations of persons with compulsory membership. Ever since the political reforms in Poland have been undertaken, professional self-government has been considered an important element of the state’s administrative system. The basis for creating such institutions was the need to protect certain professions which, in the social interest, required the highest qualifications and impeccable ethics. The professional self-government has significantly strengthened its position by taking over a number of the state’s administrative powers regarding, inter alia, the supervision of certain professions. For several years in Poland there has been a public debate on the future of the professional self-government during which arguments have been raised that question the need for the continued functioning of this type of organizations. Moreover, doubts have been raised as to whether the chambers of professional selfgovernment strengthen democratic aspirations and the development of self-governance, or whether they are anachronistic structures that threaten the consolidation of the free market order in Poland. Therefore, it is not only worth pointing out the essence and the tasks of the institution of the professional self-government, as well as its historical development in the country, but it is of paramount importance to draw attention to the significance of this type of entities in creating democratic state institutions and in accelerating participatory processes.